2004
DOI: 10.1002/ange.200460102
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Reduction of Aromatic and Aliphatic Ketones Catalyzed by Ruthenium Complexes Attached to β‐Cyclodextrin

Abstract: Wasserlösliche chirale Ru‐Komplexe mit einer β‐Cyclodextrin‐Einheit katalysieren in Gegenwart von Natriumformiat die Reduktion aliphatischer Ketone (siehe Schema) in guten bis ausgezeichneten Ausbeuten und mit bis zu 97 % ee. Die β‐Cyclodextrin‐Einheit ist für die Katalyse essenziell, denn sie trägt durch Präorganisation des Substrats im hydrophoben Hohlraum zu den außergewöhnlichen Enantioselektivitäten bei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…High enantiomeric excesses (ee) have been accomplished for a number of aromatic and aliphatic ketones in the presence of HCOONa as the hydrogen donor in water and water/ DMF mixtures, respectively. [13] We convey here an alternative strategy employing the modification of the secondary face of b-cyclodextrin 1 ( Figure 2). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…High enantiomeric excesses (ee) have been accomplished for a number of aromatic and aliphatic ketones in the presence of HCOONa as the hydrogen donor in water and water/ DMF mixtures, respectively. [13] We convey here an alternative strategy employing the modification of the secondary face of b-cyclodextrin 1 ( Figure 2). …”
mentioning
confidence: 99%
“…Surprisingly 1 H NMR experiments of this Ru complex 8 revealed no chemical shifts of the À O À CH 2 À CH 2 À NH À unit as observed when this moiety was linked to C-6 at the primary face of b-cyclodextrin. [13] Nevertheless, 8 displayed very good reactivity and high enantiomeric excess in the hydrogen transfer reaction to aliphatic ketones (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 2. Potential mechanism of hydrogen transfer from the Ru-hydride intermediate to geranyl acetone encapsulated in β-CD, adapted from [10]. Shen and Ji [11] proposed a group of catalysts based on [RuCl2(benzene)]2 and [RuCl2(mesitylene)]2 cores with eight amino alcohol-modified β-CD-based ligands as another way for the reduction of aromatic ketones.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, Schlatter et al suggested [10] the application of ruthenium complexes of the amino alcohol β-CDs as catalysts in enantioselective reduction of aromatic and aliphatic ketones. The synthetic pathway for obtaining these complexes is presented in Scheme 1.…”
Section: Cyclodextrins' Complexes With Transition Metals As Asymmetrimentioning
confidence: 99%